2007
DOI: 10.1111/j.1526-4610.2006.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention With Almotriptan: Results of the AEGIS Trial (AXERT® Early Migraine Intervention Study)

Abstract: Treatment with almotriptan within 1 hour of migraine onset resulted in significantly better clinical outcomes than placebo and tolerability similar to placebo. Acute medications, such as almotriptan, that are both effective and well tolerated may encourage patients to access acute treatment earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
82
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 32 publications
6
82
0
1
Order By: Relevance
“…6,11 The tolerability is similar in these early design treatment trials to previous almotriptan trials. [11][12][13][14][15] Adverse event rates are similar to placebo 13,16 and there was no significant difference in overall adverse event rates reported in those who treated the migraine headache early compared to late. 12,15 Only two of the four early treatment studies reported premature discontinuation rates.…”
Section: Safetymentioning
confidence: 72%
See 4 more Smart Citations
“…6,11 The tolerability is similar in these early design treatment trials to previous almotriptan trials. [11][12][13][14][15] Adverse event rates are similar to placebo 13,16 and there was no significant difference in overall adverse event rates reported in those who treated the migraine headache early compared to late. 12,15 Only two of the four early treatment studies reported premature discontinuation rates.…”
Section: Safetymentioning
confidence: 72%
“…The most common adverse effects reported in these two early intervention trials were nausea, vomiting and somnolence. 12,13 Only two studies reported serious adverse events. 12,13 The first reported three patients experiencing serious adverse events.…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations